The attitudes and perceptions of beginning teachers in relation to teaching controversial issues in the history classroom - Woolley, Mary (Revista electrónica interuniversitaria de formación del profesorado, 2017)
This paper reports on research into the attitudes and perceptions of beginning history teachers in relation to teaching controversial issues. In 2007 the UK Department for Education and Skills, alongside the Historical Association, published a report into the teaching of emotive and controversial issues in history which suggested avoidance of some topics by some teachers. Initial research was carried out with 32 beginning history teachers to explore their attitudes to teaching controversial issues in the history classroom. Ten years later, the research was repeated with a further cohort of 37 beginning history teachers to explore whether attitudes had changed. Findings showed an enthusiastic, almost moralistic group of beginning teachers, committed to sharing a wide range of views with their young audience. The beginning teachers were remarkably confident about teaching controversial issues. The area where beginning teachers lacked confidence was in dealing with parents who disagreed with their approach to teaching a certain topic. Almost all the beginning teachers thought it was appropriate for history teachers to teach topics in a way that might conflict with family or cultural values. New concerns have emerged for some beginning teachers over how to teach the history of migration in a sensitive and appropriate way. Este artículo es una investigación de las actitudes y percepciones de los profesores de historia en relación con la enseñanza de temas polémicos. En 2007, el Department for Education and Skills del Reino Unido, junto con la Historical Association, publicó un informe sobre la enseñanza de temas controvertidos en la clase de historia en el que sugirieron que algunos profesores evitaban algunos de estos temas. La investigación inicial se llevó a cabo con 32 profesores de historia principiantes para explorar sus actitudes hacia la enseñanza de temas polémicos en el aula de historia. Diez años más tarde, la investigación se repitió con una cohorte de 37 profesores de historia principiantes para comprobar si las actitudes habían cambiado. Los resultados mostraron un entusiasta, casi moralista grupo de profesores principiantes, comprometidos a compartir una amplia gama de puntos de vista con su alumnado. Los maestros principiantes estaban notablemente seguros de enseñar temas polémicos. El área donde los maestros principiantes carecían de confianza era en el trato con los padres que no estaban de acuerdo con su acercamiento a enseñar ciertos temas. Casi todos los profesores principiantes pensaron que era apropiado que los maestros de historia enseñaran temas de una manera que pudiera entrar en conflicto con los valores familiares o culturales. Nuevas preocupaciones han surgido para algunos maestros principiantes sobre cómo enseñar la historia de la migración de una manera sensible y apropiada.